2013
DOI: 10.1080/19371918.2013.774812
|View full text |Cite|
|
Sign up to set email alerts
|

Science-Based Prevention through Communities That Care: A Model of Social Work Practice for Public Health

Abstract: This paper describes a public health orientation to drug and alcohol abuse prevention; reviews the state of the science underlying a risk and protective factor approach to alcohol and drug abuse prevention; describes Communities That Care, a community practice model that makes use of this evidence; and considers how this model reflects four important principles of social work practice. The intent of this article is to provide guidance to social workers who support the National Association of Social Work’s inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 124 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…Although PROSPER and CTC are both coalition-based approaches, there are important differences between them. While PROSPER focuses on drug use prevention, CTC focuses on impacting shared risk and protective factors for multiple health and behavior problems (Haggerty and Shapiro 2013). CTC does not prescribe specific programs for parents and students, but trains the local coalition to choose from a menu of tested programs that best address the community’s profile of risk and protection.…”
mentioning
confidence: 99%
“…Although PROSPER and CTC are both coalition-based approaches, there are important differences between them. While PROSPER focuses on drug use prevention, CTC focuses on impacting shared risk and protective factors for multiple health and behavior problems (Haggerty and Shapiro 2013). CTC does not prescribe specific programs for parents and students, but trains the local coalition to choose from a menu of tested programs that best address the community’s profile of risk and protection.…”
mentioning
confidence: 99%
“…Thus, those countries that cover a broader range of family risk levels also tend to include group formats. This is not surprising, as group interventions have been identified as the most suitable for early prevention (Haggerty & Shapiro, ). Similarly to previous studies, our results support the idea that cross‐national diversity in the risk level of the target population may in part be due to different historical traditions in relation to child welfare policy and practice (Boddy et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, those countries that cover a broader range of family risk levels also tend to include group formats. This is not surprising, as group interventions have been identified as the most suitable for early prevention (Haggerty & Shapiro, 2013).…”
Section: Ta B L E 1 Service Providers Profile By Countrymentioning
confidence: 95%
“…Strengths-based social work involves engaging and leveraging resources in the individual and social environment to promote well-being (Saleebey, 2008; Simmons & Lehmann, 2013). CTC is a strengths-based approach to social work practice (Haggerty & Shapiro, 2013) that uses a risk and protective paradigm (Coie et al, 1993; Pollard, Hawkins, & Arthur, 1999) to identify individual and environmental strengths. Studies have identified protective factors in the individual, peer, family, school, and community domains shown to decrease the likelihood of problem behaviors and/or mitigate the effects of risk exposure (Bowers et al, 2011; Losel & Farrington, 2012).…”
Section: Protective Factorsmentioning
confidence: 99%